Dietary Composition of Asian Elephants in Parsa National Park: A Micro-Histological Approach - Bhattarai, Shreehari; Shah, Rubi; Bhatta, Balram (Journal of Agriculture and Forestry University, 2025)
The endangered Asian elephants face extreme threats from habitat loss and fragmentation, poaching for ivory, trophy hunting, and human-elephant conflicts. These mega-herbivores require ample forage and exhibit seasonal variations in their food intake. To analyze their diet, we collected vegetation samples through direct and indirect observations of signs such as feeding or damage, as well as dung samples from the core area and the buffer zone of Parsa National Park. A total of 30 species showed the most sign and damage categories in the core area, while 5 species were identified in the buffer zone. Micro-histological analysis of dung samples indicated that both monocots (excluding grasses) and dicots contributed significantly in the core area, whereas grasses and debris were comparatively more prevalent in the buffer zone. The availability of diet and nutritional preferences drive elephant movements and generate conflicts with local communities living in the buffer zone, especially when available habitat is shrinking and preferred species are limited in the core area. It is essential to manage the grasslands within the park by focusing on palatable, nutritious, and preferred species to achieve conservation goals for these endangered megafauna and minimize conflicts with local communities.